Dynamics and optimal Harvesting strategy for biological models with Beverton –Holt growth - Shalsh, Oday Kassim; Al-Nassir, Sadiq (Iraqi Journal of Science, 2020)
In this work, the dynamic behavior of discrete models is analyzed with Beverton- Holt function growth . All equilibria are found . The existence and local stability are investigated of all its equilibria.. The optimal harvest strategy is done for the system by using Pontryagin’s maximum principle to solve the optimality problem. Finally numerical simulations are used to solve the optimality problem and to enhance the results of mathematical analysis